Surveillance of invasive bacterial disease in Alaska, 2015 - National Center for Emerging and Zoonotic Infectious Diseases (U.S.) Division of Division of Preparedness and Emerging Infections Arctic Investigations Program
The Centers for Disease Control and Prevention's Arctic Investigations Program (AIP) in Anchorage, Alaska, maintains a statewide surveillance system for invasive diseases caused by Streptococcus pneumoniae, Haemophilus influenzae, Neisseria meningitidis, and groups A and B streptococci Laboratories throughout the state are requested to send to AIP any isolates of these organisms recovered from a blood culture, CSF, or other normally sterile site in an Alaska resident Isolate identification is confirmed and, when appropriate, serotyped and tested for antimicrobial susceptibility The objectives of this system are to provide information on disease rates within the state, monitor the emergence of antimicrobial resistance, and to monitor the effectiveness of implemented vaccine programs, such as the 23-valent pneumococcal polysaccharide vaccine, the pneumococcal conjugate vaccine and Haemophilus influenzae type b vaccines Publication date from document properties